2023
DOI: 10.3390/ani13122029
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Profiling of Amniotic Fluid, Umbilical Blood and Placenta of the Foaling Mare

Abstract: The presence of a microbiome/microbiota in the placenta is hotly debated. In previous studies, the presence of bacteria in equine amniotic fluid and umbilical blood was independent of foal health. The objective of the present study was to determine if the same bacteria are present in the equine placenta as in amniotic fluid and umbilical blood. Samples were obtained from 24 parturient mares and foals. Placental bacterial DNA was extracted, and the microbiome was identified using 16S rRNA sequencing. All amniot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This research suggested an association between placental and extraplacental (maternal oral and vaginal) microbiomes. More recently, Hemberg et al (2023) sampled the placenta after expulsion through the vaginal canal, targeting three different areas of the organ (i.e. the cervical star, the umbilical cord at the attachment of the amniotic sac, and the mid-part of the pregnant horn).…”
Section: Bacterial Presence In Fetomaternal Tissuesmentioning
confidence: 99%
See 3 more Smart Citations
“…This research suggested an association between placental and extraplacental (maternal oral and vaginal) microbiomes. More recently, Hemberg et al (2023) sampled the placenta after expulsion through the vaginal canal, targeting three different areas of the organ (i.e. the cervical star, the umbilical cord at the attachment of the amniotic sac, and the mid-part of the pregnant horn).…”
Section: Bacterial Presence In Fetomaternal Tissuesmentioning
confidence: 99%
“…the cervical star, the umbilical cord at the attachment of the amniotic sac, and the mid-part of the pregnant horn). Sequencing revealed a different bacterial composition in the three placental regions ( Hemberg et al . 2023 ), suggesting that the equine placenta might harbor a characteristic microbiome.…”
Section: Bacterial Presence In Fetomaternal Tissuesmentioning
confidence: 99%
See 2 more Smart Citations